(untitled) (Eurasian Scientific Herald, 2022)
Over the past two decades, significant progress in the treatment of children with acute lymphoblastic leukemia has been made in many countries, also in low- and middleincome countries (LMICs), but survival rates remain significantly lower than in developed countries [2,5,6]. Inadequate Accompanying therapy and the resulting high mortality from toxicity are important reasons for treatment failure in children with acute lymphoblastic leukemia in LMICs